Enhancing The Knowledge of Couples of Childbearing Age on Long-Acting Reversible Contraception (LARC) In Blabak Vilage Kediri Regency - Tety Ripursari; Putri Eka Sejati; Lely Khulafaur Rosidah; Devy Putri Nursanti; Dian Rahmawati; Wulandari, Anggrawati; Stevani Basuki Putri; Susiani Endarwati; Lia Agustin; Elen Fitriani; Wardha Oktaviani; Siska Pramita (Universitas STRADA Indonesia, 2025)
Family Planning is a program designed to regulate birth spacing and manage pregnancies, creating quality families. While good public knowledge is crucial for the program, some fertile couples still lack the use of contraception due to their inadequate knowledge of the importance of family planning, particularly reliable contraception, for regulating birth spacing. They face challenges in selecting the right contraceptive method. Twenty fertile couples participated in this activity, conducted in Blabak Village. This community service program involved providing health information. Respondents were assessed for their knowledge before and after health education. After receiving health education, participants' knowledge about reliable contraception increased significantly. Health education on family planning helps communities create happy and prosperous families.